Medicine Reminder Application: MedCare - Wong, Mann Chyi; Hazalila Kamaludin, (Applied Information Technology And Computer Science, 2024)
Medication adherence is important to help patients’ health condition always in a better situation. However, the existing reminder application has its own weakness in the functionalities offered. Thus, a medicine reminder application, MedCare, has developed to give an alternative way of reminding the medicine to be taken. It also helps the users to manage their reminder and medicine inventory. A waterfall model is used to schedule a plan for the system development process. The application is developed on Android Operating System by using Android Studio and Firebase. The medicine reminder application has been developed to provide the users with convenience of taking medicine. It can also indirectly increase the users’ health awareness by maintaining their health condition.